Regression Tests Provenance Data in the Continuous Software Engineering Context - Campos Junior, Heleno de S.; Paiva, Camila Acácio de; Braga, Regina; Araújo, Marco Antônio P.; David, José Maria N.; Campos, Fernanda (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2017: Anais do II Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2017)
Regression tests are executed after every change in software. In a software development environment that adopts Continuous Software Engineering practices such as Continuous Integration, Continuous Delivery and Continuous Deployment, software is changed, built and tested many times. Every regression test execution may include different situations and problems that are treated in isolated way. Data provenance is concerned with the origins and processes that some data has gone through, until it becomes information. Ontologies are formal models that contain axioms and relationships between classes and individuals from a specific context and can be used to infer implicit knowledge. Considering that Continuous Software Engineering activities are based on feedback cycles, in this paper, we propose an architecture based on the use of an ontology and provenance model to capture and provide regression tests data to support the continuous improvement of software testing processes. Moreover, using ontology and provenance to track execution performance and issues in this scenario, may increase the chances of those issues not happening again, since practitioners can address and solve them for future executions.